2010
DOI: 10.1089/end.2010.0049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Outcome Between Open and Robotic Surgical Repair of Recurrent Supra-Trigonal Vesico-Vaginal Fistula

Abstract: The present study suggests that robotic VVF repair is a better option for recurrent fistulas in view of its reduced morbidity, without compromising the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 12 publications
1
35
0
4
Order By: Relevance
“…In this retrospective study robotic repair significantly lowered total blood loss and shortened hospital stay by almost 2 days. In accordance with another study, no significant difference in the outcome was found 10. However, robotic surgery easily overcomes the problem of fibrosis and extensive adhesiolysis with recurrent fistulas and as such may be a better option than abdominal surgery 10 12…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this retrospective study robotic repair significantly lowered total blood loss and shortened hospital stay by almost 2 days. In accordance with another study, no significant difference in the outcome was found 10. However, robotic surgery easily overcomes the problem of fibrosis and extensive adhesiolysis with recurrent fistulas and as such may be a better option than abdominal surgery 10 12…”
Section: Discussionsupporting
confidence: 75%
“…All other studies performed the entire procedure with robotic assistance 7 8 10–12. Also, the origin of the interposed tissue was different between cases: omentum was most commonly used to separate the sutures closing the fistula 7 9 10. One applied a peritoneal inlay flap in order to prevent the time-consuming harvesting of the omentum 8.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] To overcome the challenge of free-hand laparoscopic suturing, the robotic platform has been used for a good effect as a viable surgical alternative for the management of VVF, albeit at higher costs. [7][8][9] However, the robotic platform is available at only a handful of centers in India, and hence, the open transabdominal approach and the laparoscopic approach continue to be the predominant methods of repair adopted by urologists in this country.…”
mentioning
confidence: 99%
“…We have no experience of using these techonologies. 13,14,15 CONCLUSIONS: VVF remains a devastating condition leading to physical, social and psychological trauma for the patient. Successful repair depends on the experience of surgeon, adhering to the basic surgical principles, judicious use of interposition of omental flap and avoidance of hematoma formation.…”
Section: Discussionmentioning
confidence: 99%